Effects of Ginsenoside Rg1 on Learning and Memory in a Reward‐directed Instrumental Conditioning Task in Chronic Restraint Stressed Rats. (20th October 2016) - Kezhu, Wang; Pan, Xu; Cong, Lu; Liming, Dong; Beiyue, Zhang; Jingwei, Lu; Yanyan, Yang; Xinmin, Liu
Abstract : Ginsenoside Rg1 is one of the major active ingredients of Panax ginseng and has showed notable improving learning and memory effects in several behavioral tasks, such as water maze, shuttle‐box, and step‐through, based on avoidance. However, there was no report about the role of Rg1 on the performance of reward‐directed instrumental conditioning, which could reflect the adaptive capacity to ever‐changing environments. Thus, in this study, the reward devaluation test and conditional visual discrimination task were conducted to study the ameliorating effects of Rg1 on cognitive deficits, especially the loss of adaptation capacity in chronic restraint stress (CRS) rat model. Our results showed that rat subjected to CRS became insensitive to the changes in outcome value, and it significantly harmed the rat's performance in conditional visual discrimination task. Moreover, the levels of BDNF, TrkB, and Erk phosphorylation were decreased in the prefrontal cortex of CRS rats. However, these changes were effectively reversed by Rg1 (5 and 10 mg/kg, i.p.). Therefore, it demonstrated that Rg1 has a good ability to improve learning and memory and also ameliorate impaired adaptive capacity induced by CRS. This amelioration effect of Rg1 might be mediated partially by BDNF/TrkB/Erk pathway in prefrontal cortex. Copyright © 2016 John Wiley & Sons, Ltd.